Early elective versus delayed elective surgery in acute recurrent diverticulitis: A systematic review and meta-analysis. (October 2017) - Khan, Rao Muhammad Asaf; Hajibandeh, Shahin; Hajibandeh, Shahab
Abstract: Objectives: To investigate outcomes of early versus delayed surgery in patients with acute recurrent diverticulitis. Methods: We performed a systematic review in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement standards. We conducted a search of electronic information sources, including MEDLINE; EMBASE; CINAHL; the Cochrane Central Register of Controlled Trials (CENTRAL); the World Health Organization International Clinical Trials Registry;ClinicalTrials.gov ; and ISRCTN Register, and bibliographic reference lists to identify all randomised controlled trials (RCTs) and observational studies investigating outcomes of early versus delayed surgery in patients with acute recurrent diverticulitis. We used the Newcastle-Ottawa scale to assess the risk of bias of included studies. Random-effects models were applied to calculate pooled outcome data. Results: We identified three retrospective and one prospective cohort studies enrolling a total of 1046 patients. The included patients were comparable in terms of age, ASA score and Hinchey classifications (Hinchey I and II). The results of our analyses suggested that there was no difference between two groups in surgical site infection [Odds ratio (OR) 1.61, 95% CI 0.79–3.27, P = 0.19], intra-abdominal abscess (OR 0.92, 95% CI 0.21–4.00, P = 0.91), anastomotic leak (OR1.27, 95% CI 0.50–3.25, P = 0.61), 30-day mortality [Risk difference (RD) 0.00 95% CI -0.01–0.01, P = 0.80], postoperative ileus (OR 1.35, 95% CI 0.50–3.66, P = 0.55), postoperative bleeding (OR 0.93, 95% CI 0.32–2.69, P = 0.89), ureteric injury (OR 0.62, 95% CI 0.08–5.07, P = 0.65), and overall morbidity (OR 1.42 95% CI 0.76–2.66, P = 0.27). The early surgery was associated with longer operative time [Mean Difference (MD) 12.8, 95% CI 5.08–20.53, P = 0.001] and length of stay (MD 4.41, 95% CI -0.34–8.53, P = 0.03). Among those undergoing laparoscopic surgery, conversion to open surgery was higher in the early surgery group (OR 2.71, 95% CI 1.36–5.40, P = 0.005). Conclusions: The best available evidence suggests that there is no difference between early elective and delayed elective surgery for acute recurrent diverticulitis in terms of clinical outcomes. However, longer operative time and length of stay and higher conversion rate to open surgery associated with early elective surgery may make the delayed elective surgery more cost-effective. The best available evidence is derived from non-randomised studies; therefore, high quality randomised controlled trials are required to provide more robust basis for definite conclusions. Highlights: We found no difference in clinical outcomes between early and delayed elective surgery for acute diverticulitis. Early elective surgery is associated with longer operative time and longer length of stay. Early elective surgery is associated with higher rate of conversion to open surgery. Delayed elective surgery may be more cost-effective than early elective surgery. High quality randomised controlled trials are required for definite conclusions.